Theatre as a tool to promote the culture of lawfulness. The experience of the United Nations in 3 cases (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This article aims at analyzing the power of theatre as educational tool for the prevention and fight of organized crime at global level. It identifies some major strengths and critical points of this practice, on the ground of the study of three projects developed under UNODC’s “Education for Justice” (E4J). Finally, it offers some reflections aimed at improving the use of theatre in this field.
Keywords: theatre, organized crime, prevention, education, culture of lawfulness